2022
DOI: 10.1055/a-1915-5832
|View full text |Cite
|
Sign up to set email alerts
|

Expected Versus Unexpected Delivery for Placenta Accreta Spectrum (PAS) Disorders with Same Team in Single Tertiary Center

Abstract: Objectives To evaluate the maternal and neonatal outcomes of expected and unexpected pathologically proven placenta accreta spectrum (PAS) cases in a single multidisciplinary center. Material and Methods This was a retrospective cohort study of 92 PAS cases from January 2011 until September 2021. Only cases with histopathologically invasive placentation were included in the study. The cases diagnosed at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…This may be due to the delivery planning from 35 to 36 WG to reduce the risk of severe hemorrhage. Similar results were found in previous studies [27,28].…”
Section: F O R P U B L I C a T I O Nsupporting
confidence: 93%
“…This may be due to the delivery planning from 35 to 36 WG to reduce the risk of severe hemorrhage. Similar results were found in previous studies [27,28].…”
Section: F O R P U B L I C a T I O Nsupporting
confidence: 93%
“…This is consistent with the findings of previous research where a planned delivery for PAS with a multidisciplinary team showed favourable neonatal outcomes when compared with an urgent delivery [ 18 , 20 , 23 , 35 ]. However, it is worth noting that several studies did not find significant differences in neonatal outcomes between the two delivery groups [ 25 , 36 , 37 ]. The most relevant factor influencing neonatal outcomes in women with PAS is gestational age at delivery, with higher gestational ages leading to improved neonatal outcomes [ 18 , 38 ].…”
Section: Discussionmentioning
confidence: 99%